Genetic dissection of cold stress tolerance and yield potential under cold stress in nested synthetic wheat (Triticum aestivum L.) introgression libraries using multi-locus genome-wide association and haplotype analysis - Mukesh Rathore; Nikita Aggarwal; Abhishek Pandey; Satinder Kaur; Mohd. Ashraf Bhat; Sundeep Kumar; Mohd Anwar Khan; Parvaze Ahmad Sofi; Reyazul Rouf Mir (Functional & Integrative Genomics, 2026)
Cold stress is a major abiotic constraint to wheat production in temperate regions, particularly in the Kashmir Valley of north-western Himalayas, India, where prolonged low temperatures delay growth, reduce yield, and disrupt the rice–wheat cropping system. To address this challenge, we evaluated a panel of 340 nested synthetic hexaploid wheat introgression lines, developed by introgressing allelic diversity from Aegilops tauschii and Triticum durum into bread wheat. The panel was phenotyped for cold stress tolerance, electrolyte leakage index, and yield-related traits across three temperate environments and genotyped using the 35 K Axiom® Wheat Breeder’s Array. Genome-wide association study using FarmCPU and BLINK models identified 152 stable marker–trait associations (MTAs), with − log₁₀(P) values ranging from 3.00–14.64. Several stable MTAs surpassed the Bonferroni-adjusted significance threshold and were designated as high-confidence loci. A number of stable MTAs co-localized with previously reported genomic regions, whereas others represent potentially novel loci. Multiple pleiotropic loci were detected, indicating potential for simultaneous improvement of multiple traits. Haplotype analysis identified 32 major LD blocks significantly associated with target traits, with favorable haplotypes conferring enhanced stress tolerance and productivity. Several putative candidate genes were identified within chromosome-specific LD intervals of high-confidence MTAs. Literature mining, in silico expression profiling and network analyses further supported their functional relevance in cold stress adaptation and yield regulation. The identified genomic regions, haplotypes, and candidate genes provide valuable resources for marker-assisted and haplotype-based breeding to develop cold-tolerant, high-yielding wheat cultivars suited to temperate regions, thereby supporting the sustainability of rice–wheat cropping systems.

Integrated genome-wide association study (GWAS) and metabolomics identify genetic and metabolic drivers of stripe rust resistance in wheat from the Western Himalayas - Farkhandah Jan; M. Parthiban; Sofora Jan; Anjan Kumar Pradhan; Sundeep Kumar; Safoora Shafi; Mahpara Bashir; Divya Sharma; Naeela Qureshi; Manish Kumar Vishwakarma; Sarabjit Kaur; Jaspal Kaur; et al. (Functional & Integrative Genomics, 2026)

Genome wide association studies and expression analyses identify candidate genes for spot blotch resistance in bread wheat - G. Mahendra Singh; Uttam Kumar; Bhagya Shree Acharya; Pradeep Bhati; Manish Vishwakarma; Dinesh Kumar Saini; Sundeep Kumar; Vinod K. Mishra; Arun K. Joshi; Sandeep Sharma (Theoretical and Applied Genetics, 2026)

Identification and Characterisation of Super Susceptible Bread Wheat (Triticum aestivum L.) Landraces against Leaf Rust Pathogen (Puccinia triticina Eriks.) - Naman Raj; Ujjwal Kapoor; Ramesh Bhurta; Vrinda Batra; Subhash Bijarania; Niharika Mallick; M. G. Mallikarjuna; Vaibhav Kumar Singh; Atul Kumar; Om Prakash Gangwar; Pramod Prasad; Subhash Chander Bhardwaj; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

LC-MS/MS-based discovery of new cytochalasin from fungus Rosellinia sanctae-cruciana - Nisha Sharma; Poonam Choudhary; Priya Kumari; Mohd Murtaza; Vidushi Abrol; Chetan Kumar; Rohit Singh; Sundeep Jaglan; Manoj Kushwaha (Natural Product Research, 2026)

Designing Nanocomposites of Conjugated Copolymers for the Removal of Bacterial Contamination from Polluted Water - Sundeep Kumar Dhawan; Surbhi Kohli; Ridham Dhawan; Vikas Garg; Hema Bhandari; Haritma Chopra; Badira M. Alshehri; N. S. Abd-El-Gawaad (Water, Air, & Soil Pollution, 2026)

Harnessing artificial intelligence in plant breeding: innovations in digital phenotyping and breeding methodologies - Nikita Aggarwal; Mukesh Rathore; Farkhandah Jan; Divya Sharma; Sundeep Kumar; Mahendar Thudi; Abdulqader Jighly; Rajeev K. Varshney; Reyazul Rouf Mir (Theoretical and Applied Genetics, 2026)
Agriculture plays a crucial role in the development of countries whose economies rely heavily on food production. In the face of climate change and growing global population, plant breeders are challenged to adopt more efficient crop improvement strategies. The advances in artificial intelligence (AI), particularly in large-scale data integration, analysis, and pattern recognition, have revolutionized several scientific disciplines, including plant breeding. In this review, we provide a comprehensive survey of the potential of AI tools in plant breeding with four key objectives: (i) revolutionizing high-throughput phenotyping, (ii) exploring AI-driven breeding methodologies beyond traditional approaches, (iii) optimizing breeding pipelines through improved modelling of genotype × environment × management interactions, and (iv) highlighting the limitations of AI in plant breeding and future directions. Case studies published during the past two decades illustrate successful implementations of AI-powered phenotyping and breeding frameworks for major traits across diverse crop species. Furthermore, AI tools show great promise in refining crop traits at the molecular level by increasing the accuracy and precision of emerging fields including gene editing and genomic selection. We emphasize the importance of interdisciplinary collaboration to maximize the benefits of AI in plant breeding programs and to support the sustainable and food-secure future. This review bridges the gap between AI and agricultural applications, offering a roadmap for researchers, industry professionals, and policymakers to harness information fusion and computational models for advancing precision agriculture. It will serve as a valuable resource for future plant breeding, accelerating crop improvement from phenotyping to genomic selection and breeding decision support.

Effective selection criteria for high-throughput wheat drought tolerance screening using integrated physiological and statistical approaches - Pravin pawar; Sudhir Navathe; K. J. Yashavanthakumar; Jyoti Kumari; Sundeep Kumar; P. S. Basavaraj; S. K. Singh; Gyanendra Pratap Singh; Manoj Oak (Plant Physiology Reports, 2026)

Deciphering pathological and population dynamics in Tilletia indica of Karnal bunt of wheat - Sangale Smita; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Jitender Kumar; Poulami Basak; Natasha Kashyap; Rahul Patidar; Muthyala Mahendra; Sri Ananth Kurella; Kartiki Sharma; Sundeep Kumar; Mahender Singh Saharan (Indian Phytopathology, 2025)

Genetic variability and correlation studies based on diverse wheat panel for grain yield and related attributes under north-western Himalayan conditions - Anoushka Sharma; Vijay Rana; Daizy Basandrai; Sundeep Kumar; Nimit Kumar; Ankita Mohapatra; Naiya Sharma; Anish Dhiman; Akhilesh Sharma (Vegetos, 2025)

Comprehensive analysis of genomic loci associated with glaucousness in wheat (Triticum aestivum L.) through Genome-wide association study - Shiveta Sharma; Vikas Kumar Singh; Satish Kumar; Vivek Patel; Saksham Pundir; Ajay Kumar; Sundeep Kumar; Marion S. Röder; Shailendra Sharma (Physiology and Molecular Biology of Plants, 2025)

Plant Defense Hormones: Thermoregulation and Their Role in Plant Adaptive Immunity - Zahoor Ahmad Mir; Sajad Ali; Subaya Manzoor; Divya Sharma; Deepak Sharma; Anshika Tyagi; Ab Waheed Wani; Sundeep Kumar; Belay T. Ayele (Journal of Plant Growth Regulation, 2025)

Metabolite profiling and bioactivity of fungal endofauna from Xiphinema nuragicum in the rhizosphere of Withania somnifera - Jyoti Chandan; Suruchi Gupta; Zabeer Ahmed; Shashank Kumar Singh; Puneet Kumar; Rupali Choudhary; Sundeep Jaglan; Yogesh Bharitkar; Gurleen Kour; Ekta Nehra; Ravail Singh (Environmental Science and Pollution Research, 2025)

Synthesis and Study of pH Independent L-Cysteine Capped Zirconium Oxide Quantum Dots as a Potential Bio-Imaging Probe Using HeLa Cells - Surya Pratap; Himanshu Meena; Shashi kant sharma; Vijay Kumar Sonkar; Sundeep Kumar; Horesh Kumar (Journal of Fluorescence, 2025)

Dissecting physiological traits for drought and heat tolerance in wheat - Sindhu Sareen; B. K. Meena; Ashok Sarial; Sundeep Kumar (Cereal Research Communications, 2024)

Exposure to traffic and greenspace, and associations with respiratory health in urban India - Sowmya Malamardi; Katrina Lambert; Sheetu Singh; Sundeep Salvi; Sushil K. Kabra; Meenu Singh; Shally Awasthi; Arvind Kumar Sharma; Sabir Mohammed; Thevaruparambil U. Sukumaran; Aloke G. Ghoshal; Nishtha Singh; et al. (Urban Climate, 2024)

Identification of hub genes associated with stripe rust disease in wheat through integrative transcriptome and gene-based association study - Divya Chauhan; Dwijesh Chandra Mishra; Shikha Mittal; Sushma Rani; Jyotika Bhati; Sundeep Kumar; Subhash C. Bhardwaj; Monendra Grover; Neeraj Budhlakoti; Suphiya Khan (South African Journal of Botany, 2024)

In-silico characterization of drought stress related WRKY2 transcription factor in wheat crop (Triticum aestivum L.): study of its physico-chemical properties and structural dynamics - Deepali Upadhyay; Neeraj Budhlakoti; Jyoti Kumari; Nidhee Chaudhary; Jasdeep Chatrath Padaria; Sindhu Sareen; Sundeep Kumar (Genetic Resources and Crop Evolution, 2024)

Late Quaternary deformation, strain partitioning, and fold-thrust belt widening in the Eastern Himalayan Syntaxis, India - Ishwar Singh; R. Jayangondaperumal; Arjun Pandey; Rao Singh Priyanka; Rajeeb Lochan Mishra; P. Morthekai; Shraddha Jagtap; Pradeep Srivastava; Pankaj Kumar; Sundeep Chopra (Tectonophysics, 2024)

Meta-QTL analysis in wheat: progress, challenges and opportunities - Divya Sharma; Anita Kumari; Priya Sharma; Anupma Singh; Anshu Sharma; Zahoor Ahmad Mir; Uttam Kumar; Sofora Jan; M. Parthiban; Reyazul Rouf Mir; Pradeep Bhati; Anjan Kumar Pradhan; et al. (Theoretical and Applied Genetics, 2023)

Evaluation of indigenous accessions of wheat for spot blotch resistance at the seedling and adult plant stage - Yaratha Nishith Reddy; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Mahender Singh Saharan; Sundeep Kumar; Mukesh Kumar Khokhar; Naresh Kumar; Rashmi Aggarwal (Indian Phytopathology, 2023)

Characterization of stress-induced changes in morphological, physiological and biochemical properties of Indian bread wheat (Triticum aestivum L.) under deficit irrigation - Deepali Upadhyay; Neeraj Budhlakoti; D. C. Mishra; Jyoti Kumari; Vijay Gahlaut; Nidhee Chaudhary; Jasdeep Chatrath Padaria; Sindhu Sareen; Sundeep Kumar (Genetic Resources and Crop Evolution, 2023)

Polyaniline doped silk fibroin-PCL Electrospunfiber: An electroactive fibrous sheet for full-thickness wound healing study - Ragavi Rajasekaran; Atul Kumar Ojha; Venkata Sundeep Seesala; Arman Kunwar Hansda; Nantu Dogra; Jhansi Lakshmi Parimi; Sabyasachi Roy; Ritobrata Goswami; Mamoni Banerjee; Santanu Dhara (Chemical Engineering Journal, 2023)

Molecular aspects of ABCB1 and ABCG2 in Gallbladder cancer and its clinical relevance - Nimisha; Sundeep Singh Saluja; Abhay Kumar Sharma; Phani Kumar Nekarakanti; Apurva; Arun Kumar; Real Sumayya Abdul Sattar; Hasib Anjum; Vineeta Vijay Batra; Syed Akhtar Husain (Molecular and Cellular Biochemistry, 2023)

Clinical significance of SPOP and APC gene alterations in colorectal cancer in Indian population - Asgar Ali; Nimisha; Abhay Kumar Sharma; Pramod Kumar Mishra; Sundeep Singh Saluja (Molecular Genetics and Genomics, 2023)

Exploration of Hemicellulosic Hydrolysates Derived from Arundo Donax and Cynodon Dactylon as Potential Substrates for Microbial Protein Production by Candida Tropicalis - Arushdeep Sidana; Payal Guleria; Sundeep Kaur; Sudesh Kumar Yadav (BioEnergy Research, 2023)

Comparative transcriptome profiling of near isogenic lines PBW343 and FLW29 to unravel defense related genes and pathways contributing to stripe rust resistance in wheat - Zahoor Ahmad Mir; Divya Chauhan; Anjan Kumar Pradhan; Vivek Srivastava; Divya Sharma; Neeraj Budhlakoti; Dwijesh Chandra Mishra; Vasudha Jadon; Tanmaya Kumar Sahu; Monendra Grover; Om Prakash Gangwar; Subodh Kumar; et al. (Functional & Integrative Genomics, 2023)

GWAS scans of cereal cyst nematode (Heterodera avenae) resistance in Indian wheat germplasm - Vikas Kumar Singh; Deepti Chaturvedi; Saksham Pundir; Deepak Kumar; Rajiv Sharma; Sundeep Kumar; Shiveta Sharma; Shailendra Sharma (Molecular Genetics and Genomics, 2023)

Recent advances on genome-wide association studies (GWAS) and genomic selection (GS); prospects for Fusarium head blight research in Durum wheat - Zahoor Ahmad Mir; Tilak Chandra; Anurag Saharan; Neeraj Budhlakoti; D. C. Mishra; M. S. Saharan; Reyazul Rouf Mir; Amit Kumar Singh; Soumya Sharma; V. K. Vikas; Sundeep Kumar (Molecular Biology Reports, 2023)

Evaluation of differentially expressed genic marker linked resistance gene analog (RGAs) effective at seedling stage against spot blotch in wheat - Aakash Yadav; Tilak Chandra; Sundeep Kumar (Cereal Research Communications, 2023)

Spatial distribution of fossil fuel derived CO2 over India using radiocarbon measurements in crop plants - Rajveer Sharma; Ravi Kumar Kunchala; Sunil Ojha; Pankaj Kumar; Satinath Gargari; Sundeep Chopra (Journal of Environmental Sciences, 2023)

Oral Delivery of Nucleic Acid Therapies for Local and Systemic Action - Neha Kumari; Kasturi Siddhanta; Sudipta Panja; Vineet Joshi; Chinmay Jogdeo; Ekta Kapoor; Rubayat Khan; Sai Sundeep Kollala; Balawant Kumar; Diptesh Sil; Amar B. Singh; Daryl J. Murry; et al. (Pharmaceutical Research, 2023)

Landraces-potential treasure for sustainable wheat improvement - Sneha Adhikari; Jyoti Kumari; Sherry Rachel Jacob; Pramod Prasad; O. P. Gangwar; Charu Lata; Rajnikant Thakur; Amit Kumar Singh; Ruchi Bansal; Sundeep Kumar; S. C. Bhardwaj; Subodh Kumar (Genetic Resources and Crop Evolution, 2022)

Microsatellite analysis reveals low interpopulation differentiation in velvet bean (Mucuna pruriens var. utilis) of India - Pittala Ranjith Kumar; Sai Sundeep; N. Sathyanarayana (The Nucleus, 2020)

Molecular genetic diversity analysis for heat tolerance of indigenous and exotic wheat genotypes - Sindhu Sareen; Nabin Bhusal; Manoj Kumar; Pradeep Kumar Bhati; Renu Munjal; Jyoti Kumari; Sundeep Kumar; A. K. Sarial (Journal of Plant Biochemistry and Biotechnology, 2020)

Synthesis of some novel oxazolidinone-thiazole hybrids as potential antimicrobial, antioxidant and UV mediated DNA damage protecting agents - Kamalneet Kaur; Vinod Kumar; Vikas Beniwal; Vikas Kumar; Neeraj Kumar; Vishal Sharma; Sundeep Jaglan (Medicinal Chemistry Research, 2016)

De novo transcriptome sequencing facilitates genomic resource generation in Tinospora cordifolia - Rakesh Singh; Rajesh Kumar; Ajay Kumar Mahato; Ritu Paliwal; Amit Kumar Singh; Sundeep Kumar; Soma S. Marla; Ashok Kumar; Nagendra K. Singh (Functional & Integrative Genomics, 2016)

Novel (E)-1-aryl-2-(3,5-dimethyl-4-(aryldiazenyl)-1H-pyrazol-1-yl)ethanones: solvent-free synthesis and antimicrobial, antioxidant and UV-mediated DNA damage protective activity studies - Kamalneet Kaur; Vinod Kumar; Vikas Beniwal; Vikas Kumar; K. R. Aneja; Vishal Sharma; Sundeep Jaglan (Medicinal Chemistry Research, 2015)

Solvent-free synthesis of novel (E)-2-(3,5-dimethyl-4-(aryldiazenyl)-1H-pyrazol-1-yl)-4-arylthiazoles: determination of their biological activity - Kamalneet Kaur; Vinod Kumar; Vikas Beniwal; Vikas Kumar; K. R. Aneja; Vishal Sharma; Sundeep Jaglan (Medicinal Chemistry Research, 2015)

A report of rifampin-resistant leprosy from northern and eastern India: identification and in silico analysis of molecular interactions - Sundeep Chaitanya Vedithi; Mallika Lavania; Manoj Kumar; Punit Kaur; Ravindra P. Turankar; Itu Singh; Astha Nigam; Utpal Sengupta (Medical Microbiology and Immunology, 2015)

One-pot synthesis and cytotoxic evaluation of amide-linked 1,4-disubstituted 1,2,3-bistriazoles - Kashmiri Lal; C. P. Kaushik; Krishan Kumar; Ashwani Kumar; Asif Khurshid Qazi; Abid Hamid; Sundeep Jaglan (Medicinal Chemistry Research, 2014)

CAAT box- derived polymorphism (CBDP): a novel promoter -targeted molecular marker for plants - Amit Kumar Singh; M K Rana; Sonika Singh; Sundeep Kumar; Rajesh Kumar; Rakesh Singh (Journal of Plant Biochemistry and Biotechnology, 2014)

Stem and leaf rust resistance in wild relatives of wheat with D genome (Aegilops spp.) - V. K. Vikas; M. Sivasamy; J. Kumar; P. Jayaprakash; Sundeep Kumar; R. Parimalan; Arun Kumar; Kalyani Srinivasan; J. Radhamani; Sherry Rachel Jacob; Mamata Yadav; Jyotisna Rani; et al. (Genetic Resources and Crop Evolution, 2014)

Molecular approaches for designing heat tolerant wheat - Sundeep Kumar; Prerna Kumari; Uttam Kumar; Monendra Grover; Amit Kumar Singh; Rakesh Singh; R. S. Sengar (Journal of Plant Biochemistry and Biotechnology, 2013)

Genomic characterization of drought tolerance-related traits in spring wheat - Sundeep Kumar; Sunish Kumar Sehgal; Uttam Kumar; P. V. Vara Prasad; Arun Kumar Joshi; Bikram Singh Gill (Euphytica, 2012)

Identification of QTLs for stay green trait in wheat (Triticum aestivum L.) in the ‘Chirya 3’ × ‘Sonalika’ population - Uttam Kumar; Arun K. Joshi; Maya Kumari; Rajneesh Paliwal; Sundeep Kumar; Marion S. Röder (Euphytica, 2010)

Mapping of resistance to spot blotch disease caused by Bipolaris sorokiniana in spring wheat - Uttam Kumar; Arun K. Joshi; Sundeep Kumar; Ramesh Chand; Marion S. Röder (Theoretical and Applied Genetics, 2009)